PERILAKU SEKSUAL BERISIKO PENULARAN HIV PADA TENAGA KERJA BONGKAR MUAT DI PELABUHAN KALIMAS SURABAYA - Kurnia Margawati; Arief Hargono (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2015)
HIV is a disease attacking immune system with sexual behaviors as one of its transmission media, especially for those categorized as high-risk groups. The result of Integrated Survey on Biological Behaviors (STBP) defines the TKBM (informal dockworkers) as one of these high-risk groups. The aim of this study is to identify the correlations between characteristics, knowledge, and behaviors of the dockworker on the transmission of HIV through risky sexual behaviors at Kalimas Dock, Surabaya. This study was conducted based on Cross sectional design and quantitative approach. Interview on the 52 respondents of this study was carried out by using questionnaire. This research used Simple random sampling method to chose responden on dockworkers at PT “X”, located at Kalimas Dock, Surabaya. The analysis of the research used Chi Square analysis on the collected data with signifi cance value α < 0.05. The findings of this study show dockworkers coming home frequency (p-value = 0.026; PR= 2.13), knowledge (p-value = 0.013; PR = 3.04), and attitude (p-value = 0.05, PR =2.05) correlate with transmission of HIV at Kalimas Dock. Meanwhile, other factors, such as educational background (p-value = 0.162), marital status (p-value = 0.705), and access towards HIV transmission relatedcounseling (p-value = 1) do not correlates. These findings imply several recommended that public health officers conduct counseling on preventing HIV transmission for dockworkers in order to improve theirknowledge and attitude on HIV. PT “X” should implement weekly working shift for the dockworkers so that the dockworkers could spend more time with their family.Keywords: HIV, Sexual Behavior, Dockworkers